Unraveling the World’s Longest Non-stop Migration: The Indian Ocean Crossing of the Globe Skimmer Dragonfly - Hedlund, Johanna S. U.; Lv, Hua; Lehmann, Philipp; Hu, Gao; Anderson, R. Charles; Chapman, Jason W. (Frontiers in Ecology and Evolution, 2021)
Insect migration redistributes enormous quantities of biomass, nutrients and species globally. A subset of insect migrants perform extreme long-distance journeys, requiring specialised morphological, physiological and behavioural adaptations. The migratory globe skimmer dragonfly (Pantala flavescens) is hypothesised to migrate from India across the Indian Ocean to East Africa in the autumn, with a subsequent generation thought to return to India from East Africa the following spring. Using an energetic flight model and wind trajectory analysis, we evaluate the dynamics of this proposed transoceanic migration, which is considered to be the longest regular non-stop migratory flight when accounting for body size. The energetic flight model suggests that a mixed strategy of gliding and active flapping would allow a globe skimmer to stay airborne for up to 230-286 h, assuming that the metabolic rate of gliding flight is close to that of resting. If engaged in continuous active flapping flight only, the flight time is severely reduced to ~4 h. Relying only on self-powered flight (combining active flapping and gliding), a globe skimmer could cross the Indian Ocean, but the migration would have to occur where the ocean crossing is shortest, at an exceptionally fast gliding speed and with little headwind. Consequently, we deem this scenario unlikely and suggest that wind assistance is essential for the crossing. The wind trajectory analysis reveals intra- and inter-seasonal differences in availability of favourable tailwinds, with only 15.2% of simulated migration trajectories successfully reaching land in autumn but 40.9% in spring, taking on average 127 h and 55 h respectively. Thus, there is a pronounced requirement on dragonflies to be able to select favourable winds, especially in autumn. In conclusion, a multi-generational, migratory circuit of the Indian Ocean by the globe skimmer is shown to be achievable, provided that advanced adaptations in physiological endurance, behaviour and wind selection ability are present. Given that migration over the Indian Ocean would be heavily dependent on the assistance of favourable winds, occurring during a relatively narrow time window, the proposed flyway is potentially susceptible to disruption, if wind system patterns were to be affected by climatic change.